2012
DOI: 10.1007/s00425-012-1616-z
|View full text |Cite
|
Sign up to set email alerts
|

Methylation effect on chalcone synthase gene expression determines anthocyanin pigmentation in floral tissues of two Oncidium orchid cultivars

Abstract: The anthocyanin-biosynthetic pathway was studied in flowers of Oncidium Gower Ramsey with yellow floral color and mosaic red anthocyanin in lip crests, sepals and petals, and compared with the anthocyanin biosynthesis in flowers of Oncidium Honey Dollp, a natural somatoclone derived from tissue culture of Gower Ramsey, with a yellow perianth without red anthocyanins in floral tissues. HPLC analysis revealed that the red anthocyanin in lip crests of the Gower Ramsey cultivar comprised peonidin-3-O-glucoside, de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 38 publications
0
51
0
4
Order By: Relevance
“…The widespread presence of candidate gene transcripts in all species therefore suggests that species differences in pollinator attraction, and consequently reproductive isolation, are unlikely to be caused by the simple presence or absence of expression in any candidate gene class. Rather, it may be expected that subtler changes, such as paralogue-, isoform-, or allele-specific sequence and/or expression changes, or even epigenetic phenomena [114], [115], underlie reproductive isolation. This holds true at least for SAD genes specifying alkene double-bond positions [20], [24] and appears similarly plausible for KCS and hydrocarbon chain length, where the presence of 25 transcript sequences presages complexity.…”
Section: Resultsmentioning
confidence: 99%
“…The widespread presence of candidate gene transcripts in all species therefore suggests that species differences in pollinator attraction, and consequently reproductive isolation, are unlikely to be caused by the simple presence or absence of expression in any candidate gene class. Rather, it may be expected that subtler changes, such as paralogue-, isoform-, or allele-specific sequence and/or expression changes, or even epigenetic phenomena [114], [115], underlie reproductive isolation. This holds true at least for SAD genes specifying alkene double-bond positions [20], [24] and appears similarly plausible for KCS and hydrocarbon chain length, where the presence of 25 transcript sequences presages complexity.…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, gene methylation has been observed to influence floral pigmentation. For instance, red pigmentation is observed in the flowers of the transgenic petunia line 17-R upon hypomethylation of the 35S promoter driving the A1 gene [26], while mosaic red anthocyanin in lip crests, sepals, and petals of yellow flowers of Oncidium “Gower Ramsey” may be attributed to activation of the OgCHS gene resulting from the demethylation of the five-upstream promoter region [27]. As a third example, methylation levels of MYB genes are associated with the formation of red-skinned pears and apples [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…persica “Genpei” [25]. At the same time, epigenetic modification, such as the use of hypomethylated promoters of A1 , DFR - B , and OgCHS genes driving the brick-red pelargonidin pigmentation of flower tissue [11,26,27], has been introduced to reveal genetic variation in variegated flowers.…”
Section: Introductionmentioning
confidence: 99%
“…The exploration of natural flower colour differences by means of gene expression studies is only done between a limited number of genotypes, e.g. in cyclamen [19], Ipomoea [20], Freesia hybrida [21], azalea [22,23] or Oncidium [24]. No data are currently available on the consistent effect of the studied genes in other genotypes with the same flower colour.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the quantification methods used in the aforementioned studies are not the most accurate. Some studies still describe the use of Northern blots [18,24] or semi-quantitative RT-PCR (reversed transcription PCR) [16,19,21,23,24], others do use quantitative RT-PCR (RT-qPCR) but limit themselves to the comparative Cq (quantification cycle) method [25] in combination with the use of only a single non-validated reference gene. However, multiple, assay-validated reference genes are considered to be an essential component of a consistent RT-qPCR assay [26-30].…”
Section: Introductionmentioning
confidence: 99%